ENGLISH READING AND WRITING AS AN INTERCONNECTED SKILL IN INDUSTRIAL REVOLUTION 4.0 ERA: CONCEPTUAL DEVELOPMENTS AND IMPLICATIONS TO ITS PEDAGOGY - Selnistia Hidayani (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2021)
Previous studies have demonstrated the significance of Industrial Revolution (IR) 4.0 in advancing the educational reform including in English as a foreign language (EFL) teaching and learning context. The reason is that English language remains the global lingua franca in which the top ten skills pronounced by World Economic Forum in 2016 can be achieved by good command of English. Hence, the attention devoted to the quality of students’ EFL literacy in this IR 4.0 era is more increasing than ever. Nevertheless, the issue is merely focused on the pedagogical interventions to elevate the students’ new literacies like the formulation and implementation of Education 4.0. This study aims to demystify the changing orientation of perceiving reading and writing as an interconnected skill or literacy in EFL context. The review process started from collecting relevant previous studies. Afterward, a careful reading was performed followed by synthesizing process. The findings encompass three main points: (1) the redefinition of English reading-writing connection in Industrial Revolution 4.0 era; (2) the learning resources to maximize the students’ English reading-writing competences; and (3) the implications of the changing orientations to the pedagogical practices. Recommendations for future research are also presented